Development of a clinical multi-excitation optical coherence elastography system to interrogate corneal biomechanics for the detection and staging of normotensive glaucoma - (:unkn) unknown (My University, 2026)
In Peru, Glaucoma is the first cause of irreversible blindness characterized by progressive optic nerve damage and visual field loss. It is estimated that 50% of Glaucoma Peruvian patients are not aware they carry such a disease. The primary risk factor f